PENGARUH KOMPETENSI, AKUNTABILITAS, MORALITAS INDIVIDU, TERHADAP PENCEGAHAN FRAUD DALAM PENGELOLAAN DANA DESA - Lusi Apriliyani; Nur Kholis (CV. KAMPUS AKADEMIK PUBLISING, 2023)
Preventing fraud in managing village funds is important in implementing village governance. This research aims to analyze the influence of individual competence, accountability and morality on fraud prevention. The research was carried out by distributing questionnaires to village officials in Grogol District, Sukoharjo, which consists of 14 villages. The source of data obtained in this research is primary. The data collection technique in this research is through a questionnaire. The sampling method in this research was Saturated Sampling of 98 respondents. The results of this research are that Competence, Accountability and Individual Morality have a positive effect on preventing fraud in managing village funds. Keywords: Competence, accountability, and individual morality to prevent fraud